Development and Implementation of a Combined Nurse Care Manager and Community Health Worker Training Curriculum to Address Hypertension Disparities. Issue 3 (July 2022) - Alvarez, Carmen; Ibe, Chidinma; Dietz, Katie; Carrero, Nicolas Dominguez; Avornu, Gideon; Turkson-Ocran, Ruth-Alma; Bhattarai, Jagriti; Crews, Deidra; Lipman, Paula Darby; Cooper, Lisa A.
Abstract : The use of nurse care managers (CMs) and community health workers (CHWs) has demonstrated effectiveness in supporting improved blood pressure management among racially, ethnically, and socioeconomically minoritized populations. We partnered with a community advisory board (CAB) to develop a CM and CHW training curriculum and team-based collaborative care intervention to address uncontrolled hypertension. The objective of this study was to train CMs and CHWs to implement patient-centered techniques and address social determinants of health related to hypertension control. In partnership with a CAB, we developed and implemented a training curriculum for the CM/CHW collaborative care team. The training improved CM and CHW confidence in their ability to address medical and nonmedical issues that contribute to uncontrolled hypertension in their patients; however, preexisting norms and beliefs among CMs and CHWs created challenges with teamwork. The training curriculum was feasible and well-received. Additionally, the CMs' and CHWs' reactions provided insights to improve future collaborative care training and teamwork.